PENGARUH LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN SUB SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tio Friska Simanjuntak; Yansen Siahaan; Ady Inrawan; Supitriyani Supitriyani (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2019)
The aim of this research are to determine: 1. The description of leverage, profitability, dividend policy and firm value. 2. The effect of leverage and profitability on firm value either simultaneously or partially. 3. The ability of dividend policy to moderated leverage and profitability relationship with firm value at Sub Sector Property and Real Estate on The Indonesia Stock Exchange partially. The result of the research can be summarized as follows: 1. Leverage, profitability, dividend policy and firm value has decreased. 2. The results of multiple linear regression test without moderating is known that leverage and profitability has a positive effect on firm value. 3. The results of multiple linear regression test with moderating variable is known that dividend policy weakens the relationship of leverage with firm value, while dividend policy strengthens the relationship of profitability with firm value. 4. The results of the first hypothesis test can be concluded that leverage and profitability have significant effect on firm value either simultaneously and partially. 5. The second hypothesis test results can be concluded that partially dividend policy can moderate but has no significant relationship of leverage with firm value while dividend policy can moderate has significant relationship of profitability with firm value. This research suggest that company should manage assets efficiently, increase company profit, and increase dividend distribution so that firm value will also increase. Keywords: Leverage, Profitability, Dividend Policy and Firm Value